Effects of Physical Exercise on the Expression of MicroRNAs: A Systematic Review. Issue 1 (January 2020) - Silva, Franciele Cascaes da; Iop, Rodrigo da Rosa; Andrade, Alexandro; Costa, Vitor Pereira; Gutierres Filho, Paulo José Barbosa; Silva, Rudney da
Abstract : Abstract: Silva, FCd, Iop, RdR, Andrade, A, Costa, VP, Gutierres Filho, PJB, and Silva, Rd. Effects of physical exercise on the expression of microRNAs: A systematic review 34(1): 270–280, 2020—Studies have detected changes in the expression of miRNAs after physical exercise, which brings new insight into the molecular control of adaptation to exercise. Therefore, the objective of the current systematic review of experimental and quasiexperimental studies published in the past 10 years was to assess evidence related to acute effects, chronic effects, and both acute and chronic effects of physical exercise on miRNA expression in humans, as well as its functions, evaluated in serum, plasma, whole blood, saliva, or muscle biopsy. For this purpose, the following electronic databases were selected: MEDLINE by Pubmed, SCOPUS, Web of Science, and also a manual search in references of the selected articles to April 2017. Experimental and quasiexperimental studies were included. Results indicate that, of the 345 studies retrieved, 40 studies met the inclusion criteria and two articles were included as a result of the manual search. The 42 studies were analyzed, and it can be observed acute and chronic effects of physical exercises (aerobic and resistance) on the expression of several miRNAs in healthy subjects, athletes, young, elderly and in patients with congestive heart failure, chronic kidney disease, diabetes mellitus type 2 associated with morbid obesity, prediabetic, and patients with intermittent claudication. It is safe to assume that miRNA changes, both in muscle tissues and bodily fluids, are presumably associated with the benefits induced by acute and chronic physical exercise. Thus, a better understanding of changes in miRNAs as a response to physical exercise might contribute to the development of miRNAs as therapeutic targets for the improvement of exercise capacity in individuals with any given disease. However, additional studies are necessary to draw accurate conclusions.